Memikirkan Kembali Misi Trinitaris : Perspektif Lesslie Newbigin Dan Johan Herman Bavinck - Doni Herwanto Harianja; Antonius S. Un (STTRII, 2020)
This article is an overview of the ideas of Lesslie Newbigin and Johan Herman Bavinck in thinking about the basis of the Trinity on a theology of mission. These two missionaries agreed to base their mission on the doctrine of the Trinity. The mission-based on the doctrine of Trinity is the mission that does not distinguish between the gospel and social justice or